FORECASTING ANALYSIS OF RICE AVAILABILITY AND DEMAND IN LAMPUNG PROVINCE - Adilla, Ummu; Rosanti, Novi; Haryono, Dwi (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Lampung Province's population is growing yearly at an average rate of 1.10%. The need for rice in the province of Lampung will continue to increase as the population increases. However, the increase in rice production needs to be balanced with the population growth rate. This study aims to describe the availability and needs of rice in Lampung Province and project the availability and needs of rice in Lampung Province. The method used in this research is descriptive quantitative with a secondary data analysis approach using time series data from 2002 – 2022. The data analysis method used is descriptive quantitative and forecasting using ARIMA. The results showed that the availability and needs in Lampung Province over the past 20 years have always experienced a surplus. The increase in the amount of rice was achieved through the programs launched by the Ministry of Agriculture, including the UPSUS program and the Farmers Success Card. Rice availability and demand in Lampung Province will increase from 2022 - 2032. The results of the forecast of rice availability in Lampung Province increased significantly, where in 2022, it was 1,967,866.72 tons, and in 2032, it could reach 2,075,982.18 tons. Lampung Province's rice demand is predicted to increase significantly, where in 2022, it was 1,005,054.35 tons to 1,314,276.61 in 2032.